The Use of Toothbrushing Educational Videos to Improve Oral Hygiene Among Students of Elementary School - Niakurniawati, Niakurniawati; Imran, Herry (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
The use of educational videos can motivate students to improve oral hygiene by observing and practicing what they see and hear. Preliminary observations conducted on 10 fifth-grade students revealed that 8 of them had poor oral hygiene status, with an average score of 3.2. This study aimed to determine the effect of toothbrushing educational videos on oral hygiene among students of SDN 54 Banda Aceh. This study employed a quasi-experimental design using a one-group pretest–posttest approach. Data were collected through oral hygiene examinations conducted before and after the educational intervention on May 9 and May 15, 2024. The study population consisted of fifth-grade students, with a total sample of 48 students selected using random sampling. Data were analyzed using the paired t-test. Before the intervention, the majority of students (43 students; 89.6%) had moderate oral hygiene status. After receiving the toothbrushing educational video, most students (36 students; 75%) showed good oral hygiene status. The results indicated a significant difference before and after the intervention (p-value = 0.000), with a mean difference of 13.1. In conclusion, the use of toothbrushing educational videos significantly improves oral hygiene among students. Students are encouraged to enhance their knowledge by actively reading and learning about oral and dental health.Keywords: toothbrushing; educational video; oral hygiene; elementary school students